Morpho-genetic Evaluation of Rice Genotypes (Oryza sativa L.) Including Some Varieties and Advanced Lines Based on Yield and Its Attributes - Hannan, Afsana; Islam, Md. Mukidul; Rahman, Muhammad Saifur; Hoque, Md. Najmol; Sagor , G H M (Journal of the Bangladesh Agricultural University, 2024)
In breeding programs, direct selection based on yield is very difficult due its polygenic nature. Therefore, breeders need to consider association of numerous yield related attributes with yield and among themselves. In this study, 43 rice genotypes including some released varieties and advanced lines were evaluated based on morpho-genetic parameters. A field experiment was conducted at the field laboratory of Genetics and Plant Breeding Department, Bangladesh Agricultural University using a randomized complete block design with three replications. Analysis of variance revealed that all genotypes exhibited significant variations (P ≤ 0.001) for all considered traits except leaf length indicating a wider extent of variability for selection. Greater phenotypic coefficient of variation (PCV) compared to corresponding genotypic coefficient of variation (GCV) for all the traits representing environmental influence on the studied traits. High GCV and PCV values were observed for the most important yield related traits like seedling height, leaf length, flag leaf area, flag leaf angle, number of effective tiller hill-1, 1000-grain weight and yield plant-1. These results suggested that selecting genotypes with these traits could be way for attaining enhancement in rice yield. Majority of the traits displayed high heritability (>60%) with high genetic advance (>20%) pointing towards non-additive gene action suggesting selection should be practiced carefully. Correlation study explored significant positive and negative association among yield and related attributes. Principal component analysis revealed the most important traits contributing to the variations among the genotypes. According to cluster analysis, 43 genotypes were grouped into 4 clusters among which genotypes within cluster I and cluster III might be selected for future rice breeding programs regarding yield potentiality and other related traits. J Bangladesh Agril Univ 18(4): 923–933, 2020 https://doi.org/10.5455/JBAU.9328